2021
DOI: 10.1016/j.jpeds.2021.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Pediatric Readiness and Potentially Avoidable Transfers

Abstract: Objective To determine the association between potentially avoidable transfers (PATs) and emergency department (ED) pediatric readiness scores and the score's associated components. Study designThis cross-sectional study linked the 2012 National Pediatric Readiness Project assessment with individual encounter data from California's statewide ED and inpatient databases during the years 2011-2013. A probabilistic linkage, followed by deterministic heuristics, linked pretransfer, and post-transfer encounters. App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…a Generalized estimating equations (GEE) model using year as a factor to account for within-subject variability across the years 2017-2020. Diagnostic categories within this population are similar to prior studies of non-IHS and tribal EDs, including those in rural settings, with most pediatric patients being transferred for respiratory concerns, injuries, poisonings, or gastrointestinal or neurologic concerns 5,15,20,21. Respiratory concerns accounted for 18.9%-26.7% of transfers and 39% of these (199/507) were discharged directly from the receiving ED suggesting a potential area for pediatric readiness initiatives geared toward quality improvement and enhancedTA B L E 3Generalized estimating equations (GEE) model using year and age as factors to account for within-subject variability across the years 2017-2020.Abbreviations: ICU, intensive care unit; IHS, Indian Health Service; LOS, length of stay.TA B L E 4 Top 5 diagnostic categories by year.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…a Generalized estimating equations (GEE) model using year as a factor to account for within-subject variability across the years 2017-2020. Diagnostic categories within this population are similar to prior studies of non-IHS and tribal EDs, including those in rural settings, with most pediatric patients being transferred for respiratory concerns, injuries, poisonings, or gastrointestinal or neurologic concerns 5,15,20,21. Respiratory concerns accounted for 18.9%-26.7% of transfers and 39% of these (199/507) were discharged directly from the receiving ED suggesting a potential area for pediatric readiness initiatives geared toward quality improvement and enhancedTA B L E 3Generalized estimating equations (GEE) model using year and age as factors to account for within-subject variability across the years 2017-2020.Abbreviations: ICU, intensive care unit; IHS, Indian Health Service; LOS, length of stay.TA B L E 4 Top 5 diagnostic categories by year.…”
mentioning
confidence: 61%
“…It is possible that this is secondary to a reduced number of pediatric-trained providers and ancillary staff in the community setting. 12 There was a significant increase in transfers in the 15 [13][14][15][16][17] IHS and tribal EDs have previously scored an average of 60.9/100 (lower than the national average) on assessments of pediatric readiness and noted areas of improvement within these systems have included quality improvement, stocking of pediatricspecific equipment, policies and procedures for interfacility transport, and maintaining staff pediatric competencies. 10,18 Our study highlights potential targets for maximal impact for interventions aiming to enhance pediatric readiness in IHS and tribal EDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The designation of a PECC seems to be instrumental in achieving a higher score, and centers with high PR have lower likelihood to transfer patients. 24,25 More recently, data from the NPRP and National Trauma Databank have been combined to evaluate the association of PR, trauma designation, and WPRS on mortality and complications. This study found a pediatric trauma mortality rate of 1.5% and complication rate of 1.3%, which were both significantly lower in higher WPRS centers (odds ratio, 0.58 and 0.88, respectively).…”
Section: Pr For Trauma Centers and Injured Childrenmentioning
confidence: 99%
“…State-based questionnaires specific to the comfort of emergency professionals with pediatric trauma resuscitation procedures and protocols have demonstrated significant gaps in the PR of nontrauma centers 23 . The designation of a PECC seems to be instrumental in achieving a higher score, and centers with high PR have lower likelihood to transfer patients 24,25 . More recently, data from the NPRP and National Trauma Databank have been combined to evaluate the association of PR, trauma designation, and WPRS on mortality and complications.…”
Section: Pr For Trauma Centers and Injured Childrenmentioning
confidence: 99%